The colloquial register in the informative text: between the journalistic style and the communicative strategy - Vellón Lahoz, Javier (Estudios sobre el Mensaje Periodístico, 2012)
The presence of the colloquial register in the journalistic informative texts is due to variables linked with factors of the speech: internal (section, kind, topic, subjectivity) and contextual (type of newspaper, relationship with the addressee, lines of communicative action, company project). The use of linguistic resources of conversational nature in the informative account aimed at establishing a balance between the explanatory rigour of the news, guaranteed by the standard variety of the language, and the emotive component, of an idiomatic and socializer character, that singularizes the journalistic style in a period in which it seeks to define its area of influence on a very competitive communication market.
Keywords: Colloquial record; journalistic language; standard variety; informative kinds; journalistic style